Doctors' experiences and their perception of the most stressful aspects of complaints processes in the UK: an analysis of qualitative survey data. Issue 7 (4th July 2016) - Bourne, Tom; Vanderhaegen, Joke; Vranken, Renilt; Wynants, Laure; De Cock, Bavo; Peters, Mike; Timmerman, Dirk; Van Calster, Ben; Jalmbrant, Maria; Van Audenhove, Chantal
Abstract : Objectives: To examine doctors' experiences of complaints, including which aspects are most stressful. We also investigated how doctors felt complaints processes could be improved. Design and methods: A qualitative study based on a cross-sectional survey of members of the British Medical Association (BMA). We asked the following: (1) Try to summarise as best as you can your experience of the complaints process and how it made you feel. (2) What were the most stressful aspects of the complaint? (3) What would you improve in the complaints system? Participants: We sent the survey to 95 636 doctors, and received 10 930 (11.4%) responses. Of these, 6146 had a previous, recent or current complaint and 3417 (31.3%) of these respondents answered questions 1 and 2. We randomly selected 1000 answers for analysis, and included 100 using the saturation principle. Of this cohort, 93 responses for question 3 were available. Main results: Doctors frequently reported feeling powerless, emotionally distressed, and experiencing negative feelings towards both those managing complaints and the complainants themselves. Many felt unsupported, fearful of the consequences and that the complaint was unfair. The most stressful aspects were the prolonged duration and unpredictability of procedures, managerial incompetence, poor communication and perceiving that processes are biased in favour of complainants. Many reported practising defensively or considering changing career after a complaint, and few found any positive outcomes from complaints investigations. Physicians suggested procedures should be more transparent, competently managed, time limited, and that there should be an open dialogue with complainants and policies for dealing with vexatious complaints. Some felt more support for doctors was needed. Conclusions: Complaints seriously impact on doctors' psychological wellbeing, and are associated with defensive practise. This is not beneficial to patient care. To improve procedures, doctors propose they are simplified, time limited and more transparent.